Reading Chinese Fortune Cookie The Making of Chinese American Rhetoric - Mao, LuMing (University Press of Colorado, 2006)
LuMing Mao offers an important discussion of the rhetoric of Chinese American speakers, which has wide implications for the teaching of writing in English and for our understanding of cross-cultural influences in discourse. Recent scholarship tends to explain such influences as contributing to language hybridity---an advance over the traditional "deficit model." But Mao suggests that the "hybridity" approach is perhaps too arid or sanitized, missing rich nuances of mutual exchange, resistance, or even subversion. Working from Ang's concept of "togetherness in difference," Mao suggests that speakers of hybrid discourse may not be attempting the standard (and failing), but instead may be deliberately importing cultural material to create a distance between themselves and the standard. This practice, over time, becomes a process that transforms English, enriching and enlarging it through the infusion of non-Western discourse features, subverting power structures, and even providing unique humorous touches. Of interest to scholars in composition, cultural studies, and linguistics as well, Reading Chinese Fortune Cookie leads in an important new direction for both our understanding and our teaching of English.